Kepemimpinan Transformasional Kepala Sekolah dan Regulasi Emosi Guru SD dalam Menghadapi Tuntutan Pembelajaran Anak Usia Dasar: Studi Fenomenologi - Asrina Yeni; Riswandi Riswandi; Siti Rahma Sari (Institut Agama Islam Daruttaqwa Gresik, 2026)
Elementary school teachers face increasing pedagogical and emotional demands as they respond to diverse student characteristics, learning targets, administrative responsibilities, classroom discipline, and limited facilities. These pressures make teacher emotion regulation a crucial issue in elementary education, yet it is often discussed as an individual capacity rather than as a practice shaped by school leadership. This study aims to explore the lived experiences of teachers and the principal in understanding the meaning of transformational leadership in supporting elementary school teachers’ emotion regulation. A qualitative phenomenological approach was employed at SD 11 Way Ratai. Data were collected through in-depth interviews with five informants, consisting of teachers and the principal, then analyzed manually through transcription, repeated reading, coding, theme grouping, interpretation, and formulation of experiential essences. The findings show that the principal’s transformational leadership is experienced through role modeling, motivational support, professional guidance, open listening, appreciation, and attention to teachers’ personal and professional needs. Such leadership helps teachers calm themselves, control their tone of voice, reinterpret student behavior, avoid impulsive anger, and choose more personal and educative approaches in learning. The study also reveals that teacher emotion regulation is not merely self-regulation, but socially supported regulation embedded in a humane and collaborative school climate. These findings contribute to the development of elementary school leadership studies by shifting attention from performance-oriented leadership to emotionally responsive leadership. The practical implication is that principals need to institutionalize emotional support, reflective communication, teacher appreciation, and professional collaboration as part of sustainable quality of learning in elementary schools.